Transparency, Trust, and Accountability in AI-Driven Accounting: A Critical Literature Review - Selvi Agustina; Ria Wulandari (LPPM STIE Kasih Bangsa, 2025)
This qualitative literature review explores the ethical challenges associated with transparency, trust, and accountability in AI-driven accounting. The study synthesizes findings from recent research to highlight the complexities of integrating AI technologies into accounting practices. Transparency is identified as crucial for ensuring that AI systems are understandable and scrutinizable by stakeholders. Trust is essential for the acceptance and effectiveness of AI systems, necessitating clear communication about AI processes and limitations. Accountability requires robust governance frameworks and shared responsibility between humans and AI systems. The review underscores the need for interdisciplinary collaboration to develop comprehensive frameworks addressing ethical, legal, and technical aspects. Despite its contributions, the study acknowledges limitations, including the evolving nature of AI and the need for empirical studies to examine long-term impacts. Future research should focus on developing practical solutions to enhance transparency, trust, and accountability in AI-driven accounting.